Penjadwalan Proyek Konstruksi Dengan Penerapan Simulasi Monte Carlo - Dian Febrianti; Bambang Tripoli; Zakia Zakia; Rahmat Djamaluddin (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
The scheduling method that is often used in project planning in a deterministic way is the CPM method, the PERT method. However, in reality, uncertainty is often found in project completion, in accordance with the characteristics of a construction project that has a high level of risk. One of the methods used to determine the estimated project time is the monte carlo simulation method. The monte carlo simulation is a statistical sampling technique used to estimate solutions to quantitative problems. The research was conducted on the construction project of the Public Service Center (PSC) building in Krueng Sabee District, Aceh Jaya Regency. The purpose of this study is to determine the probabilistic method of scheduling and to explain the application of the monte carlo method for scheduling. The data used in this study are secondary data in the form of interviews and project implementation time schedule (curve S). Based on the monte carlo simulation that has carried out the distribution of completion on a public service center building construction project, the minimum value of the total project duration is 86.40 days, the maximum value of the total project duration is 105 days, and the mean value is 96 days. So the project can be completed within 96 days of the 100 plan days. So it can be concluded that the project is completed 4 days faster than the 100 day plan. Based on the above explanation, the Monte Carlo simulation is not significant enough to reduce the project duration, so that more significant work can be added or overtime. Keywords— Scheduling, Probabilistic, Simulation, Monte Carlo